A Literature Review on Personality, Creativity and Innovative Behavior - Abdullah, Iqra; Omar, Rozeyta; Panatik, Siti Aisyha (International Review of Management and Marketing, 2016)
Personality has been conceptualized from a host of theoretical perspectives. The present conceptual paper is an endeavor to enhance and grab the etymology of personality, innovative behavior and creativity. Moreover relationship of personality with creativity and innovative behavior is explored in depth. After reviewing an extensive literature, the researcher came up with the general accepted taxonomy of personality measure i.e. widely accepted framework named as big five inventory (BFI). While, innovative behavior was gauged by the yardstick of three phases namely idea generation, gathering support and idea implementation. It was suggested for the future researchers to explore the more innovative measures for this overlooked relationship in study of personality and innovative behavior. Keywords: Personality, Extraversion, Conscientiousness, Agreeableness, Neuroticism, Openness to Experience, Innovation, Creativity, Innovative Behavior JEL Classifications: D3, M12, 031